Lacanian coordinates : from the logic of the signifier to the paradoxes of guilt and desire - Wolf, Bogdan (Karnac, 2015)
Psychoanalysis is an experience of truths and lies in language. It is also a discourse, and a praxis. Lacanian Coordinates takes the reader from the beginning of Lacan's teaching, from the logic of the signifier and the Lacanian subject, to the drive and object a, qua object a, the paradoxes of guilt, and finally to the desire of the Other, love, and femininity - the themes explored and developed in the second volume of Lacanian Coordinates (2015). Volume One explores the points of Lacanian orientation that lead us to the particularity of the subject, and considers whether we find them not solely in the discourse of the universal, to which religion, science and philosophy testify, but also in the analytic experience itself. Psychoanalysis creates conditions for an encounter with an analyst and with words forgotten, neglected, underestimated, yet also bursting with meaning and surprises. Each chapter contributes to this subjective realisation, taking as reference the clinic, the voice of an analysand, and everyday discourse. An ethics that emerges from this experience is not of the superego but of a speaking being faced with the non-existence of an all-knowing and all-powerful Other.